Comparative Bioavailability of Two Oral L-Thyroxine Formulations after Multiple Dose Administration in Patients with Hypothyroidism and its Relation with Therapeutic Endpoints and Dissolution Profiles - Vaisman, Mário; Spina, Luciana Diniz Carneiro; Eksterman, Leonardo F.; Santos, Mario José Carneiro Felipe dos; Lima, Jaderson Sócrates; Volpato, Nadia Maria; Silva, Regina Lengruber da; Brito, Ana Paula Pereira de; Noël, Franćois (Arzneimittelforschung, 2001)
The aim of the present study was to evaluate the bioequivalence and thera peutic equivalence of the two most com monly prescribed L thyroxine (monso dium L thyroxine hydrate, CAS 25416-65-3) formulations in Brazil in patients treated for hypothyroidism. Twenty four patients received 100 µg L thyroxine daily of either Puran T4® (test) or the Brazilian reference formulation (refer ence) during 42 days, in a two period crossover design. Serum samples ob tained over a 24 h interval were analyzed for their total T4 concentration by a chemiluminescent immunoassay. Con tent and uniformity of the tablets and dis solution studies were also assessed ac cording to USP 24 monograph using an isocratic HPLC UV system and a rotating-paddle method. The mean pharmaco-kinetic parameters for total T4, expressed as geometric means (CV), for the test and reference were, respectively: Cmax (µg/dl) 9.8 (14.3 %) and 10.8 (14.9 %); AUC0–24 h (µg/dl · h) 206.8 (13.9 %) and 230.4 (14.9 %). Median values (90 % CI) for Tmax (h) were 3 (2–3) and 2 (2–4) for the test and reference, respectively. 90 % CI for ratios of LogCmax and LogAUC0–24h were 86.6–94.9 and 86.3–93.4, respectively. Although the test exhibited values of Cmax and AUC0–24 h around 10 % lower than the reference, these formulations must be considered bioequivalent since the 90 % CI for both Cmax and AUC0–24h mean ratio were within the 80–125 % interval as proposed by the US Food and Drug Administration and the Brazilian legislation. TSH dosages within the normal range further support therapeutic equivalence between the two formulations. Dissolution data were roughly in agreement with in vivo results since both formulations comply with the USP dissolution criteria although the test tablets had a slower dissolution rate than the reference tablets. As a conclusion, the two oral formulations of L-thyroxine are both bioequivalent and therapeutically equivalent although presenting a small difference in their extent of absorption. Noteworthy, the dissolution profiles of the tablets correlate well with their bioavailability in the present experimental conditions.
Keywords: CAS 25416-65-3; Hypothyroidism; Puran T4®; Thyroxine, bioavailability, bioequivalence, dissolution